ANALISIS PERLINDUNGAN TERHADAP TOLERANSI KEBEBASAN BERAGAMA DI INDONESIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Setyawan, Nathanael Bagas; Arifin, Ridwan (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Activities to religion are generally carried out by all religious communities in the world without limiting an activity in the process, because it can disrupt the worship process. But in its implementation, especially in Indonesia, the public is less aware of the importance of tolerating religious freedom in order to prevent religious conflicts in the concept of Human Rights. Historically, religious problems are a social problem because they involve the lives of people who cannot be separated from the study of social sciences. Therefore, the religious sciences are essentially parts of Sociology, Psychology and Anthropology. Whereas the issue of religious intolerance in Indonesia is a crucial problem, because these problems can divide the Indonesian people, even though religious problems are a problem that does not need to be exaggerated because in essence every religion teaches good things so that the issue of religious freedom of others is in vain. So from that a country needs to have a law to regulate the existing government system, one of which is to regulate religion in Indonesia. Religion in Indonesia itself has been regulated in chapter XI of Religion in Article 29 paragraph (2) where the State guarantees the independence of each resident to embrace their respective religion and to worship according to that belief. Not only about religious freedom, the context of violations concerning religion in Indonesia has also been regulated in law, but the public still underestimates the law because they themselves are also taboo on the laws that apply in Indonesia. Problems concerning religious intolerance can be prevented through counseling on vulnerable areas that will cause religious commotion, so that the pillars of nationality contained in the Pancasila can still survive and run as they should. This study analyzes the Protection of Religious Freedom in Indonesia in the perspective of Human Rights in Indonesia. Keywords : Agama, intoleransi, konflik, kebebasan, perlindungan hukum.